A generational relational model of nature and mental wellbeing: results of a qualitative analysis - Bunce, Hannah L. I.; Owens, Matthew (Frontiers in Psychology, 2025)
IntroductionThere is a developing evidence base for the benefits of natural environments for health and mental wellbeing. However, given the increasing urbanisation of our planet and subsequent disconnection from our natural world, there is a danger that we may ultimately suffer from a nature ‘generational amnesia’. The facets and mechanisms underpinning these relationships are poorly understood and theoretical frameworks are needed to aid further research. There is a paucity of research into the lived experiences of people with good wellbeing and their nature experiences, which has the potential to elucidate key elements of the nature-wellbeing relationship.MethodsThe current study used a qualitative design to explore themes concerning the lived experiences with nature, of 12 people with self-reported good wellbeing. Semi-structured interviews were carried out and data were analysed using thematic analysis.ResultsTwo overarching themes of human-nature relationship and self-regulation encapsulated the data. Within the first, there were two superordinate themes of developmental and nature interconnectedness. Self-regulation consisted of managing health and flourishing.DiscussionA theoretical model is proposed to help better understand these relational themes in a generational context. The model is informed by Cognitive Analytic Therapy and attachment theory and generates testable hypotheses for future research.